Pulls of international student mobility - Martin Kahanec; Renáta Králiková (Institute for the Study of Labor (IZA), 2011)
Economic theory suggests that high-skilled immigration generally has positive effects on the receiving economy. International student mobility is an important channel through which high-skilled immigrants arrive. The purpose of this paper is to identify some of the key determinants of international student mobility among higher education policies. For this purpose we review the existing evidence and compile a longitudinal dataset covering inflows of international students into a number of advanced economies. We then study the effects of various higher education policies on the inflow of international students using parametric as well as non-parametric statistical methods. We conclude that among higher education policies especially the quality of higher education institutions and the availability of programs taught in the English language can act as an important tool to attract international students, and thus high-skilled migrants.
urn:nbn:de:101:1-201202285025
Keywords: I23; I28; J21; J24; J61; J68; 330; higher education; education policy; migration; migration policy; student mobility; Studierende; Auslandsaufenthalt; Hochschulpolitik; Hochqualifizierte Arbeitskräfte; Internationale Wanderung; Migrationspolitik; Industriestaaten